Dampak Penyelenggaraan KTT Archipelagic and Island States Forum 2023 Terhadap Pariwisata di Bali - Adinatha, Ida Ayu Devina Radharani; Priadarsini, Ni Wayan Rainy (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2025)
This study aims to measure the impact of the 2023 Archipelagic and Island States (AIS) Forum Summit on Bali's tourism sector. Employing a qualitative approach, this research analyzes both primary and secondary data to identify significant changes occurring after the summit. The findings reveal that the AIS Forum made a substantial positive contribution to Bali's economic growth, particularly in the tourism sector. Notably, increased hotel occupancy rates, a surge in tourist arrivals, and local economic growth were observed as direct impacts. Furthermore, the summit played a crucial role in promoting Bali as a sustainable tourism destination, with a particular focus on marine tourism through the concept of the blue economy.